2018
DOI: 10.1002/pra2.2018.14505501054
|View full text |Cite
|
Sign up to set email alerts
|

Towards a more inclusive technical website: Knowledge gaps, performance, experience, and perception differences among various user groups

Abstract: This paper reports a usability and user experience research study of http://PBCore.org, a WGBH website supporting the PBCore metadata dictionary. Usability testing was conducted with 53 participants who worked in audiovisual processing and archiving. Significant differences in task performances and interaction experiences among user groups were found, most notably between broadcast and information professionals, archivists/librarians and other staff, and participants who had an LIS degree and those who did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Task performance and user experience can vary due to education, training background, and expertise (Tang et al, 2018). In many cases, experts may perform a task faster than novices, but differences may not be observed in terms of task accuracy, and graphical representations can reduce effort (Dillon & Song, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Task performance and user experience can vary due to education, training background, and expertise (Tang et al, 2018). In many cases, experts may perform a task faster than novices, but differences may not be observed in terms of task accuracy, and graphical representations can reduce effort (Dillon & Song, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Much of the usability literature employs quantitative measures of task performance, with experienced or expert users generally accomplishing usability tasks faster than novice users (Dillon & Song, 1997; Ooms et al, 2012; Tüzün et al, 2016). The question of how task performance and interaction experiences differ based on user groups has been addressed by Tang et al (2018), who reported differences between broadcast and information professionals, archivists/librarians, and other staff, and those with a library and information science (LIS) degree and those without. Reading preferences may also affect users' search behaviors (Anna & Pertti, 2017).…”
Section: Introductionmentioning
confidence: 99%